(untitled) (The International Journal for Scientific Research, 2026)
The current study aimed to identify post-traumatic stress from the perspective of individual services and its relationship to the family roles of Palestinian families under Israeli attacks. The descriptive analytical approach was followed, as it was suitable for the nature of the study, using the social survey method with a sample of (40) Palestinian families in the Qalqilya Governorate. The results of the study indicated that the percentage of response to the overall score regarding post-traumatic stress from the perspective of individual services and its relationship to the family roles of Palestinian families under Israeli attacks was very high, as indicated by the percentage (74.10%). It also showed a strong positive relationship between post-traumatic stress from the perspective of individual services and the family roles of Palestinian families under Israeli attacks. The study reached several recommendations, the most important of which is the development of early intervention programs that focus on providing psychological support to individuals and families to help them get rid of negative thoughts and painful memories related to the traumas, by providing strategies to enhance focus and make appropriate decisions to cope with them.